2022
DOI: 10.1021/acs.langmuir.2c03057
|View full text |Cite
|
Sign up to set email alerts
|

Developing High-Performance In-Plane Flexible Aqueous Zinc-Ion Batteries with Laser-Scribed Carbon-Supported All Electrodeposited Electrodes

Abstract: Developing high-performance, safer, and affordable flexible batteries is of urgent need to power the fast-growing flexible electronics market. In this respect, zinc-ion chemistry employing aqueous-based electrolytes represents a promising combination considering the safety, cost efficiency, and both high energy and high-power output. Herein, we represent a highperformance flexible in-plane aqueous zinc-ion miniaturized battery constructed with all electrodeposited electrodes, i.e., MnO 2 cathode and zinc anode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The assessment of δ-MnO 2 NPs by the aforementioned techniques and its comparison with other similarly fashioned catalysts (Table S2) indicate the range of employing it as a catalyst in other electrocatalytic applications. Moreover, the MnO 2 NPs are widely used for battery and supercapacitor applications as compared to HER.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of δ-MnO 2 NPs by the aforementioned techniques and its comparison with other similarly fashioned catalysts (Table S2) indicate the range of employing it as a catalyst in other electrocatalytic applications. Moreover, the MnO 2 NPs are widely used for battery and supercapacitor applications as compared to HER.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, lithium costs and electrolyte toxicity further hamper the application of LIB in flexible technologies. [322,[379][380][381][382][383] Thus, thin film electrode battery cells have become increasingly desirable within this context, and laser processing has been employed over the years in several tasks, from electrode cutting, annealing, or structuring. [384] Alongside electrode processing by lasers, printing technologies have also been increasingly explored in thin battery concepts, for current collectors, electrolyte, and separator printing, to avoid physical vapor deposition under vacuum of metal electrode material (e.g., aluminum and copper).…”
Section: Batteriesmentioning
confidence: 99%
“…[250] In a very elegant way, Yadav et al address this issue, by assembling a flexible zinc-ion battery (ZIB) based on DLW-engineered current collectors followed by electrodeposition of active materials. [379,382] The team laser-scribed interdigitated electrodes on PI followed by the electrodeposition of vanadium oxide and zinc. The obtained aqueous rechargeable ZIB exhibited a high initial capacity of 556 mAh g −1 at a current density of 0.1 A g −1 , even after considerable mechanical deformation tests, [379] showing comparable performance with other cells reported in the literature using other synthesis and assemblies methods.…”
Section: Batteriesmentioning
confidence: 99%
“…44 Recently we have shown the fabrication of a Zn//MnO 2 fullcell in-plane flexible battery with laser-scribed carbon supporting all electrodeposited electrodes, which showed a high capacity of 196 mAh/g at 1 A/g current after 1350 cycles, accompanied by excellent flexibility. 45 Wang et al 46 reported on the fabrication of a Zn//Zn x V 2 O 5 microbattery by electrodepositing layered M x V 2 O 5 onto a three-dimensional (3D) nanoporous Au microcurrent collector. The hydrated cation-preintercalated electrodes in a symmetric configuration showed a high volumetric energy density of ∼358 mWh/cm 3 .…”
Section: ■ Introductionmentioning
confidence: 99%